PENINGKATAN HASIL BELAJAR SISWA SMP NEGERI 14 KOTA BOGOR TENTANG TEKS PROSEDUR MELALUI PENERAPAN MODEL PEMBELAJARAN MAKE A MATCH - Nina Rohani (Universitas Pakuan, 2021)
IMPROVING THE LEARNING OUTCOMES OF JUNIOR HIGH SCHOOL STUDENTS ABOUT PROCEDURE TEXTS THROUGH THE APPLICATION OF THE MAKE A MATCH LEARNING MODELThis research departs from the phenomenon that occurs in the classroom that the low quality of Indonesian language learning can have an influence on student learning outcomes. Therefore, a teacher needs to consider a learning model that is in accordance with the learning material so that it can improve student learning outcomes. One of the learning models tested through this research is the Make a Match learning model. The research was carried out in class 7F of SMP Negeri 14 Bogor City in Semester I of the 2019/2020 Academic Year and aimed to (1) find out the Make a Match learning model can improve student learning outcomes about procedural texts, (2) describe the process of improving student learning outcomes about procedure text after applying the Make a Match learning model, (3) measuring the magnitude of the increase in student learning outcomes about procedure text after applying the Make a Match learning model The results of this study indicate that the application of the Make a Match learning model about procedure text in class 7F of SMP Negeri 14 Bogor before applying the Make a Match learning model had an average score of 68.94. When learning was changed by applying the Make a Match learning model, the average student learning outcomes increased to 78.24 in the first cycle and 86.12 in the second cycle. It was concluded that the application of the Make a Match learning model used by the teacher could improve student learning outcomes, therefore the researcher suggested that the application of the Make a Match learning model should be socialized and used in Indonesian language learning in schools within the Bogor City Education Office.